Pengaruh Word of Mouth, Brand, Awareness dan Strategi Marketing Mix terhadap Keputusan Pembelian Produk Air Minum dalam Kemasan di Tanjungpinang Bintan - Istikhomah, Istikhomah; Iranita, Iranita; Paramita, Bunga (Program Studi Manajemen FEBM UMRAH, 2023)
This study aims to prove the influence of word of mouth, brand awareness and marketing mix strategies on purchasing decisions. The population in this study is all the people of Tanjungpinang City and Bintan Regency, totaling 395,928 people in 2022. Sampling uses a probability sampling technique. The sample in this study were the people of Tanjungpinang-Bintan who had consumed bottled drinking water (AMDK) found in the Tanjungpinang-Bintan area when the questionnaire was distributed. This type of research is quantitative research. Primary research data comes from questionnaires. The data collected and tested using Smart PLS 3 Software. The results of the study found that brand awareness has an effect and is not significant on purchasing decisions and the marketing mix strategy has no effect and is not significant on purchasing decisions. Based on the results of the hypothesis test, the influential and significant value is found in the word of mouth variable (X1) on purchasing decisions (Y), obtained a t-statistic value of 3.834 > t-table 1.66 and a p-value of 0.000 < a significance value of 0.05. Based on the results of the determination coefficient test or goodness of fit (R²) a value of 0.369 (36.9%) was obtained, indicating that this research model was moderate because it was able to explain 39.6% of the entire study. While the remaining 60.4% is explained by other variables not examined in this study.